2019
DOI: 10.1186/s42047-019-0031-1
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of high PD-L1 expression is low in lung adenocarcinoma patients from Northeast Brazil

Abstract: Background As Immune checkpoint inhibitors (ICPIs) are changing the standard-care in lung cancer with good clinical activities and durable responses, its indication must be based on the appropriate patient selection once only a fraction of patients has a response to these costly drugs. In larger cohorts the expression of programmed cell death–ligand 1 (PD-L1) has been associated with good clinical response of ICPIs in lung adenocarcinoma where the rate of high PD-L1 expression (defined as PD-L1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
1
2
3
Order By: Relevance
“…Alves da Silva et al 38 evaluated the PD-L1 expression in LC patients from the northeast region of Brazil and observed a similar proportion of positivity (40.5% v 35.1% in our study). The prevalence of tumors scoring from 1% to 50% or less and 50% or more was also similar between both studies (24% v 21.2% and 16.5% v 13.8%, respectively).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Alves da Silva et al 38 evaluated the PD-L1 expression in LC patients from the northeast region of Brazil and observed a similar proportion of positivity (40.5% v 35.1% in our study). The prevalence of tumors scoring from 1% to 50% or less and 50% or more was also similar between both studies (24% v 21.2% and 16.5% v 13.8%, respectively).…”
Section: Discussionsupporting
confidence: 84%
“…In Brazil, the only study to assess ALK expression was performed in the northeast region. 38 The authors found a much higher prevalence of ALK-positive tumors (13.3% compared with 4% in our study). 38 A recent report that included samples from nine countries in Latin America found that the prevalence of ALK rearrangements ranged from 4.1% (Colombia) to 10.8% (Peru).…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…The prevalence of (PD-L1) of TPS ≥ 1% in a large multicenter study from different continents was 52% in Europe, 53% in Asia-Pacific, 47% in the Americas, and 55% in other countries but ours was 45% which is comparable to the Americas, slightly lower than European countries but higher than in a Brazilian study which had 24 % (8) and an Indian study (34%) (16). However, only stage IIIB/ IV cases of NSCLC were included in the large multicenter study (15).…”
Section: Resultscontrasting
confidence: 55%
“…In a study by Yang et al [23], it was discovered that there was no correlation between PD-L1 expression and driver mutations, such as EGFR and ALK. However, Zhang et al [20] discovered a correlation between PD-L1 and EGFR but not ALK, and Sliva et al discovered a correlation between PD-L1 and ALK [24]. This discovery suggests that patients with various tissue types and driver gene mutations may respond to ICI therapy differently, although this has to be proven in more research.…”
Section: Discussionmentioning
confidence: 99%